Evaluation and development of an image-guided radiotherapy protocol for prostate and nodes. Issue 1 (17th February 2017) - Hutton, Nicky; Baker, Angela; Naismith, Olivia; Carver, Antony; Jessop, Anne
Abstract: Purpose: To evaluate and develop an image-guided radiotherapy (IGRT) protocol for the effective treatment of prostate and pelvic lymph nodes. Methods and materials: This study comprised of nine patients receiving radiotherapy for node negative prostate cancer, who had a pair of planar kV images taken for 37 treatment fractions. The positioning accuracy for both implanted fiducial markers and pelvic bony anatomy (surrogate for pelvic node position) was calculated using random and systematic errors. Appropriate margins were also determined. All patients followed a strict bladder and bowel protocol before computed tomography planning and treatment. Results: In total, 292 sets of images were used for fiducial marker and pelvic bone registration. A discrepancy of >5 mm between the fiducial markers and the anatomical pelvic bone was seen in 4% of treatment sessions. The maximum displacement observed between the fiducial match and the bone match was 7, 10 and 4 mm in the A/P (anterior/posterior), S/I (superior/inferior) and R/L (right/left) directions, respectively. Conclusion: The margins used in combination with an online IGRT strategy ensure both the fiducial match and the bone match correlate within 5 mm thus allows good coverage of both prostate and nodal target volumes. It is essential that this is combined with a strict bladder and rectal preparation protocol to ensure accuracy and reproducibility.